2019
DOI: 10.1519/ssc.0000000000000492
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Training Load and Its Implementation in Tactical Populations: A Narrative Review

Abstract: Tactical populations often participate in demanding physical training and perform strenuous workplace tasks, increasing injury risk. Mitigating injury risk is vital for maintaining trained personnel and should be a focus for tactical populations. One such method, tracking training load, has not been studied in-depth in tactical populations, despite documented effectiveness in elite sport. Most injuries to tactical personnel are overuse in nature and therefore may be prevented by optimizing training load. A c c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…GPS units, heart rate monitors, etc.) that can track training load and intensity (49). A simple way in which the strength and conditioning coach can track the intensity of training exercises and sessions in recruits is via rating or perceived exertion (RPE).…”
Section: ***Insert Table 1 About Here***mentioning
confidence: 99%
“…GPS units, heart rate monitors, etc.) that can track training load and intensity (49). A simple way in which the strength and conditioning coach can track the intensity of training exercises and sessions in recruits is via rating or perceived exertion (RPE).…”
Section: ***Insert Table 1 About Here***mentioning
confidence: 99%
“…High-impact activity both from combat training and drills and carrying heavy loads may also increase stress on the knee joint in this population [34]. On this basis, the reconditioning program for the injured site needs to consider the overall training load that the soldier is subject to [35], noting that some of these loads will come from the soldier's general military training and work requirements [36].…”
Section: Discussionmentioning
confidence: 99%
“…Copp et al, found military personnel skipped breakfast [42], and Rahmani et al, reported an inverse association between healthy eating and odds of depression and anxiety [56]. Based on the available evidence, while overall energy and carbohydrate intake appears to be suboptimal, further exploration on the freeliving type and timing of dietary energy and carbohydrate intake in tactical occupations is warranted [2].…”
Section: Suboptimal Free-living Energy and Carbohydrate Intakementioning
confidence: 99%
“…Optimizing dietary recommendations, and subsequent intake, to support health, well-being and performance is important for tactical personnel [1]. Tactical occupations, including military, law enforcement, and fire and rescue emergency services (SES) [2], have many important dietary considerations and challenges. Several studies have reported sedentary behaviors, chronic disease risk, and obesity rates similar to, or higher than, those seen at a population level [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%